Repair technology of hydro-technical buildings - Anufryeva, E. V. (Science and Transport Progress, 2011)
The article is dealt with basic statements of the developed technology of recovering the supporting power of transport and hydraulic structures. The proposed pneumatic jet method of repair and recovery of the supporting power of transport and hydraulic structures permits saving 30…40 per cent of cement, increasing the cement density and hence decreasing the mass of structures.